2018
DOI: 10.1002/tea.21518
|View full text |Cite
|
Sign up to set email alerts
|

Teleology as a tacit dimension of teaching and learning evolution: A sociological approach to classroom interaction in science education

Abstract: Teleology has been described as an intuitive cognitive bias and as a major type of student conception. There is controversy regarding whether teleological explanations are a central obstacle to, are legitimate in, or are even supportive of science learning. However, interaction in science classrooms has not yet been investigated with regard to teleology. Consequently, this study addresses the question of how teleological explanations emerge in science classroom interactions about evolution and how teachers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 74 publications
3
38
0
2
Order By: Relevance
“…This type of ambiguous teaching practice is not restricted to the teaching sequences analyzed in this paper; it can also be found in grade 12 high school classes (Gresch and Martens 2019), which suggests that the presented interactions can also be observed in other classes taught by different teachers. Although there is some evidence that teleological explanations are more frequent at a younger age (Kelemen 1999;Zohar and Ginossar 1998), the teaching practices in the presented seventh-grade unit are comparable to similar types of teaching practices in high school classes.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…This type of ambiguous teaching practice is not restricted to the teaching sequences analyzed in this paper; it can also be found in grade 12 high school classes (Gresch and Martens 2019), which suggests that the presented interactions can also be observed in other classes taught by different teachers. Although there is some evidence that teleological explanations are more frequent at a younger age (Kelemen 1999;Zohar and Ginossar 1998), the teaching practices in the presented seventh-grade unit are comparable to similar types of teaching practices in high school classes.…”
Section: Discussionmentioning
confidence: 67%
“…Although there is some evidence that teleological explanations are more frequent at a younger age (Kelemen 1999;Zohar and Ginossar 1998), the teaching practices in the presented seventh-grade unit are comparable to similar types of teaching practices in high school classes. In contrast, teachers of a different type of teaching habitus (Gresch and Martens 2019) reject teleological explanations throughout the unit. Classroom interactions are structured by a polarization of correct student answers, scientific explanations and Darwin's evolutionary theory on the one hand and incorrect student answers, teleological explanations and Lamarck's evolutionary theory on the other hand.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although instructors’ construal-consistent language might have the potential to both reinforce construal-consistent misconceptions about biology and serve as a pedagogical tool in science education, little research has investigated whether instructors use construal-consistent language in the biology classroom, and the handful of studies largely focus on high school settings. These studies have demonstrated that high school teachers use teleological language when teaching biology (see, e.g., Nehm and Schonfeld, 2007; Gresch and Martens, 2019). The use of cognitive construals in undergraduate biology classrooms and the prevalence of anthropic and essentialist language in biology classrooms remain underinvestigated.…”
Section: Introductionmentioning
confidence: 99%